Unraveling the core symptoms of mental health in senior grade three students- a network analysis - Fang, Guoxiang; Wang, Ying; Yuan, Huiling; Yan, Ne; Zhi, Shaomin (Frontiers in Psychiatry, 2024)
Background: Adolescence is not only an important transitional period of many developmental challenges, but also a high risk period for mental health problems.Psychotherapy is recommended for mental health problems in adolescents, but its effectiveness is not always satisfactory. One possible contributing factor may be the lack of clarity surrounding core symptoms.Methods: In this study, we investigated the mental health status of senior grade three students, a group of adolescents facing college entrance exams, by the Middle School Student Mental Health Test (MHT) and analyzed the core symptoms by network analysis. This study was conducted through an online survey platform (www.xiaodongai.com) from 15 February 2023 to 28 March 2024. The subjects scanned a QR code with their mobile phone to receive the questionnaire.Results: The mean age of these 625 students were 18.11 ± 2.90 years. There are 238 male participants and 387 female participants. 107 individuals scored above 56 (107/461, 23.2%), with individual scale scores over 8 up to over 60% of participating students. Notably, the top three prominent symptoms were "academic anxiety", "allergic tendency" and "somatic symptoms". However, upon conducting network analysis, it became evident that three strongest edges in this network were "somatic symptoms" and "impulsive tendency", "academic anxiety" and "social anxiety" as well as "social anxiety" and "Loneliness tendency". "somatic symptoms", "social anxiety" and "self blame tendency" exerted the highest expected influence. This 3 suggests that, statistically speaking, these three symptoms exhibited the strongest interconnections within the network.Limitation: cross-sectional analysis; Bias in self-reported variables.Conclusion: These findings can deepen the knowledge of mental health among senior grade three students and provide some implications (i.e., targeting symptoms having highest expected influence) for clinical prevention and intervention to address the mental health needs of this particular group.